Classical and Non-classical Presentations of Complement Factor I Deficiency: Two Contrasting Cases Diagnosed via Genetic and Genomic Methods - Shields, Adrian M.; Pagnamenta, Alistair T.; Pollard, Andrew J.; , OxClinWGS; Taylor, Jenny C.; Allroggen, Holger; Patel, Smita Y.; Taylor, Jenny C.; Knight, Samantha J. L.; Pagnamenta, Alistair T.; Popitsch, Niko; Camps, Carme; et al. (Frontiers in Immunology, 2019)
Abstract Deficiency of complement factor I is a rare immunodeficiency that typically presents with increased susceptibility to encapsulated bacterial infections. However, non-infectious presentations including rheumatological, dermatological and neurological disease are increasingly recognised and require a high-index of suspicion to reach a timely diagnosis. Herein, we present two contrasting cases of complement factor I deficiency: one presenting in childhood with invasive pneumococcal disease, diagnosed using conventional immunoassays and genetics and the second presenting in adolescence with recurrent sterile neuroinflammation, diagnosed via a genomic approach. Our report and review of the literature highlight the wide spectrum of clinical presentations associated with CFI deficiency and the power of genomic medicine to inform rare disease diagnoses.